Reading mathematical graphs about pollution: Exploring the role of mathematical beliefs - Doria, Luca; Scalvini, Cristina (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
Graphs are the most used tools to communicate data about pollution, climate change and other socio-environmental issues, but research in mathematics education warns us that people in general and students in particular find it difficult to read them. Our hypothesis is that affect-related elements play a key role in influencing how students read and understand mathematical graphs and in this paper we investigate the role of beliefs in shaping the way students approach graphs about pollution. Different views about mathematics emerge when students have to account for why they find a graph beautiful or clear.